PENGARUH PERBEDAAN KEPADATAN POPULASIRhyzopertha dominicaTERHADAP JENIS DAN KERUSAKAN SEREALIA - Harahap, Nafsiyah Agustina (Biospecies, 2025)
The study aimed to determine the effect ofRhyzopertha dominicapopulation density on thetype and extent of damage to cereals. The study was conducted at the Plant Pests andDiseases Laboratory, Agroecotechnology Study Program, Faculty of Agriculture,Malikussaleh University. The study was conducted in the form of alaboratory experimentwith two types of treatments arranged in a Completely Randomized Design. The cereal typetreatment consisted of two levels, namely sorghum and wheat. The types of cereal varietiesused in the study were the tropical wheat variety Dewata and the sorghum variety Super-2obtained from the Cereal Crops Research Institute, Maros, South Sulawesi. The populationdensity treatment ofR. dominicaconsisted of four levels, namely 5, 10, 15, and 20 pairs ofadults per 150 g of cereal. Each treatment combination was repeated three times, so thatthere were 24 experimental units.The results showed that increasing the population densityofR. dominicasignificantly affected the number of F1, the percentage of cereal damage, theamount of powder, andweight loss during storage. The density of 20 pairs of adultsproduced the highest number of F1 and damage. Cereal type also influenced theseparameters, with wheat showing higher levels of damage than sorghum, indicating thatwheat is preferred byR. dominica.However, there was no significant interaction betweenpopulation density and cereal type on any of the observed parameters. Data were analyzedusing analysis of variance and the DMRT test at the 0.05 level.